Catalisadores bimetálicos Pt-Fe/CeO2 para a reação de oxidação preferencial do CO - Mattos, Luciana Vieira (2010)
The objective of this work is to study the preferential oxidation (PROX) of carbon monoxide in H2-rich feed streams over Pt-Fe/CeO2 catalysts in a feed gas composed of 3% CO, 1.5% O2, 80% H2, and N2 (for balance). The temperature effect (in the 100-300ºC range) and the Pt and Fe load ones were also analyzed. In order to further understand those catalysts performance, a study comparing them to the monometallic Pt/CeO2 and Fe/CeO2 catalysts, both prepared identically with the same Pt and Fe loading, was conducted. The catalysts were prepared by wet impregnation and the support by the hydrothermal method. The solids were characterized by X-Ray Diffraction (XRD), B.E.T Surface Area and Temperature Programmed Reduction (TPR). The catalytic reaction experiments were conducted under atmospheric pressure. The results pointed that the activity and selectivity curves of the Pt/CeO2 catalysts showed a decrease on the 100 -200ºC temperature range. Conversely, both curves of conversion and selectivity became increasingly above 200ºC, suggesting the occurrence of the water-gas shift reaction (WGSR). The 0.6% Pt/CeO2 catalyst was not only the most active at 200ºC but also the most selective in the whole temperature range for the PROX reaction. Furthermore, an increase in CO conversion was shown by all promoted catalysts, in which the 3% Pt catalyst presented the strongest promoter effect, with a significant increase on both CO conversion and selectivity.